Growth Pattern of Certain MPTS Raised on Sodic Land - Rana, B. S.; Parihar, A. K. S.; Singh, B. P. (Indian Forester, 2002)
A total of 13 tree species (MPTS) were planted on sodic land in 1987. Soil profile (upto 1m depth) revealed silt clay loam texture of the soil indicating high pH. Soil organic carbon content and nutrients (N, P and K) declined with increase in soil depth. Of the total species planted, four species viz., Casuarina equisetifolia, Eucalyptus hyhrid, Dalbergia sissoo and Leucaena leucocephala reflected conceivably better growth than rest of the species. Total tree biomass attained by afore-mentioned species at the eight year age was in the order : L. leucocephala (199.6 t ha-1 ) > C. equisetifolia (197.3 t ha-1 ) > Eucalyptus hybrid (136.6 t ha-1 ) > D. sissoo (62.2 t ha-1).